T189. FREE THYROXIN CONCENTRATIONS MODERATE THE RESPONSE TO A COGNITIVE REMEDIATION THERAPY IN PEOPLE WITH EARLY PSYCHOSIS: PRELIMINARY FINDINGS. (18th May 2020) - Estrada, Francesc; Maria Crosas, Josep; Ahuir, Maribel; Pérez, Sara; Zabala, Wanda; Aguayo, Raquel; David Barbero, Juan; Montalvo, Itziar; Tost, Meritxell; Llauradó, Laura; Guàrdia, Armand; Palao, Diego; et al.
Abstract: Background: Cognitive deficits are a common cause of functional disability in people with psychotic disorders. Cognitive remediation produces moderate improvements in cognitive performance in people with schizophrenia, although there is variability in the responses between patients. As previous longitudinal studies suggest that free thyroxin (FT4) levels influence attention cognitive tasks in patients with early psychosis, we aimed to conduct a pilot study to explore whether thyroid hormones might predict the response to cognitive remediation therapy (CRT) in patients with first-episode psychosis. Methods: 27 patients (8 women; 19 men) with first-episode psychosis aged between 18 and 35 years old were randomized to receive a computerized CRT for three months (2 sessions/week) (N=14) or treatment as usual (TAU) (N=13). A full cognitive battery (CANTAB Schizophrenia) was administered at baseline and follow-up (3 months later, after the CRT/TAU period). Plasma levels of thyroid-stimulating hormone (TSH) and FT4 were measured. Data were analyzed on an intention-to-treat basis. Correlation analyses were conducted to explore the association between TSH and FT4 levels and cognitive changes over time. An ANOVA for repeated measures was used to compare longitudinal changes over time by the experimental group while adjusting for TSH and FT4 levels. Significance was defined as p<0.05. Results: TSH concentrations were not associated with cognitive changes over time. FT4 concentrations were associated with cognitive worsening over time in cognitive tasks dealing with reaction time (simple median movement time [r= 0.60, p= 0.003]; simple median reaction time [r= 0.44, p= 0.039]), sustained attention (signal detection for the rapid visual processing task [r= -0.46, p= 0.028]) and verbal memory (immediate recognition [r= -0.54, p= 0.008]; delayed recognition [r= -0.48, p= 0.019]). The ANOVA for repeated measures did not show time by group effects although a time by FT4 significant effect was found for cognitive tasks dealing with these cognitive domains (p<0.05 for all). Discussion: Although a direct effect of the CRT on cognitive improvement was not found, baseline FT4 concentrations appeared to predict the response to CRT in people with early psychosis. Significant associations were found for cognitive domains dealing with attention processes, which are in accordance with previous studies exploring the association between thyroid function and cognitive functioning in early psychotic patients. Our preliminary findings suggest that the determination of thyroid function status might be important for establishing which patients could show cognitive improvements over time. If these results are replicated in larger studies, the determination of thyroid status might help identify those individuals more prone for showing cognitive improvements, and allowing the implementation of a personalized medicine approach in the field of cognitive rehabilitation in psychosis.